Rheology, hydration, and strength evolution of interground limestone cement containing PCE dispersant and high volume supplementary cementitious materials. (5th August 2017) - Mehdipour, Iman; Kumar, Aditya; Khayat, Kamal H.
Abstract: The aim of this paper is to elucidate fundamental composition-reaction-property correlations in blended binder systems prepared with Portland-limestone cement (PLC) and high volume of aluminosilicate supplementary cementitious materials (SCMs). An extensive investigation involving coordinated experiments and numerical simulations was carried out to quantify synergistic interactions between PLC and SCM (i.e., fly ash and slag), and benchmark them against corresponding blended ordinary Portland cement (OPC) systems. The study was carried out on mortars provisioned with optimum dosages of polycarboxylate ether (PCE) dispersant to improve fluidity and achieve enhanced particle packing. The results indicate that in spite of incorporating PCE at high dosages, PLC systems consistently show greater hydration kinetics compared to their OPC counterparts on account of their higher specific surface area. The SCMs are more effective in terms of improving strength in PLC systems as compared to OPC systems. This superiority of the PLC systems over OPC systems is attributed to enhanced particle packing and the carbonate-rich chemistry of PLC which allows enhanced formation of space-filling carboaluminate hydrates. Further, the results are consolidated to develop reliable correlations between hydration kinetics, rheological properties, and strength evolution for OPC-SCM and PLC-SCM systems. These correlations provide insights into optimizing binder formulation and proportioning. Graphical abstract: Highlights: Portland limestone cement develops faster rates and larger extents of hydration compared to their OPC counterparts. SCMs are more effective at improving strength in PLC compared to OPC systems due to formation of space-filling hydrates. Hydration kinetics is well-correlated with evolution of rheological properties and strength development of cementing systems. Composition-reaction-property correlations provide insights into optimizing binder formulation to enhance performance.